Correction: Nally et al. The Effectiveness of School-Based Interventions on Obesity-Related Behaviours in Primary School Children: A Systematic Review and Meta-Analysis of Randomised Controlled Trials. Children 2021, 8, 489 - Sarah Nally; Angela Carlin; Nicole E. Blackburn; Judith S. Baird; Jo Salmon; Marie H. Murphy; Alison M. Gallagher (Children)
We acknowledge an error in the BMI data in our publication [...]